(3GdQjGVjGJ GdeJbOeI ddegfOSjfs - (3GdHOhj, GdSjO YHO GdeYWjs ((3HjQhJ (B:s (3OGQ GdQGJH GdLGeYjI,s, 1985)
(3GdOhGd GdOhQjI heJSdSdI ahQjQ(B.s
Keywords: (3GdOhGd (B((3QjGVjGJ(B)s -- (3JMdjds; (3JMdjd GdSdGSd GdRefjIs